1994
DOI: 10.1002/jbm.820281213
|View full text |Cite
|
Sign up to set email alerts
|

Study of the surface characteristics of magnetron‐sputter calcium phosphate coatings

Abstract: Plasma-sprayed hydroxylapatite coatings on metals such as titanium have been investigated for many years and have shown a good biocompatibility when implanted in bony tissues. Radiofrequency magnetron sputtering was used as an alternative method to deposit thin films of hydroxylapatite on titanium substrates. X-ray diffraction demonstrated that the sputtered layer was crystalline with a preferred (001) crystallographic orientation with the C-axis perpendicular to the substrate surface. Scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(114 citation statements)
references
References 17 publications
5
108
0
1
Order By: Relevance
“…An RF power of 150 W resulted in an HA thin film that including both characteristics from the RF powers of 200 W and 250 W. This clearly indicated that the relative intensities of the XRD pattern depend on the processing conditions, which explains why a preferred orientation could result from a specific RF power. Wolke showed that a film coated at an RF power of 700 W had characteristics of the (002) preferred orientation when a sample rotation was applied [6]. In our study, the HA coating processed with sample rotation resulted in a preferred orientation when an RF power of 250 W was applied, and the coating process therefore led to an HA thin film with a characteristic in the preferred orientation, which was highly affected by the sample rotation and RF power.…”
Section: Resultssupporting
confidence: 46%
See 1 more Smart Citation
“…An RF power of 150 W resulted in an HA thin film that including both characteristics from the RF powers of 200 W and 250 W. This clearly indicated that the relative intensities of the XRD pattern depend on the processing conditions, which explains why a preferred orientation could result from a specific RF power. Wolke showed that a film coated at an RF power of 700 W had characteristics of the (002) preferred orientation when a sample rotation was applied [6]. In our study, the HA coating processed with sample rotation resulted in a preferred orientation when an RF power of 250 W was applied, and the coating process therefore led to an HA thin film with a characteristic in the preferred orientation, which was highly affected by the sample rotation and RF power.…”
Section: Resultssupporting
confidence: 46%
“…HA-coating via RF magnetron sputtering leads to uniformity in the chemical composition and density of the film. The preferred orientation and the amorphous properties of the thin films can be determined by adjusting the processing conditions during RF magnetron sputtering [6,7]. For example, the amorphous HA films can be transformed to crystalline thin films by heating, further increasing the spread of human osteoblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Films were deposited in a custom-built sputter deposition chamber at room temperature. This technique shows strong HA titanium bonding associated with outward diffusion of titanium into the HA layer, forming TiO 2 at the interface (Wolke et al, 1994).…”
Section: Sputter Depositionmentioning
confidence: 99%
“…The final sur face roughness of these FA-HA coatings was Ra = 9.59 |im. Further, of the implants with a diameter of 4.0 mm, 18 were left uncoated (cpTi) and 18 were provided with an amorphous Ca-P (Ca-P-a) coating using a radiofrequency (rf) magnetron sputter process (van Dijk et al 1995a(van Dijk et al , 1995bWolke et al 1994). These implants were not gritblasted, but were argon-etched before sputter coat ing.…”
Section: Implant Materials and Coating Characteristicsmentioning
confidence: 99%